2019
DOI: 10.1002/jbmr.3894
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Disease Progression Does Not Decrease Intestinal Phosphorus Absorption in a Rat Model of Chronic Kidney Disease–Mineral Bone Disorder

Abstract: The Cy/+ rat has been characterized as a progressive model of chronic kidney disease-mineral bone disorder (CKD-MBD). We aimed to determine the effect of kidney disease progression on intestinal phosphorus absorption and whole-body phosphorus balance in this model. A total of 48 Cy/+ (CKD) and 48 normal littermates (NL) rats were studied at two ages: 20 weeks and 30 weeks, to model progressive kidney function decline at approximately 50% and 20% of normal kidney function. Sodiumdependent and sodium-independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 36 publications
6
23
0
Order By: Relevance
“…OVX also resulted in a non-significant trend towards lower whole-body phosphorus and calcium balance. In a separate study of Cy/+ and WT male rats, we found that phosphorus and calcium balance are also marginally lower in Cy/+ males with CKD compared to normal WT controls 44 . The lower phosphorus and calcium balance in the present study is likely reflective of the loss of bone mass in the OVX rats compared with Sham.…”
Section: Discussionmentioning
confidence: 68%
“…OVX also resulted in a non-significant trend towards lower whole-body phosphorus and calcium balance. In a separate study of Cy/+ and WT male rats, we found that phosphorus and calcium balance are also marginally lower in Cy/+ males with CKD compared to normal WT controls 44 . The lower phosphorus and calcium balance in the present study is likely reflective of the loss of bone mass in the OVX rats compared with Sham.…”
Section: Discussionmentioning
confidence: 68%
“…Composition of the diets is in online supplementary Table 1. CKD and NL were given 3 different diets (n = 8-11 rats per group): (1) AC group: AC grain diet from birth to 28 week, studied at Indiana, (2) AC + Casein group: AC grain diet until 17 weeks then casein diet until 28 weeks, studied at Indiana, (3) Non-AC + Casein group: Non-AC grain from birth to 16 weeks then switched to casein diet until 30 week of age, studied at Purdue [8]. All groups had access to water and food ad libitum light-dark cycle from 6 a.m. to 6 p.m. At the end of the studies, rats were anesthetized with isoflurane, the thoracic cavity was opened, blood collected from the vena cava resulting in death, and intestinal tissues were collected (online suppl.…”
Section: Animalsmentioning
confidence: 99%
“…For the AC and AC + Casein groups, at 28 weeks, duodenum and jejunum were dissected according to Moe et al [4] and for the Non-AC + Casein according to Vorland et al [8]. Tissues were flushed with 0.9% saline using a gavage needle to remove luminal contents, cut transversally with scissors, the mucosa scraped with microscope cover slip, and the tissue placed in a microcentrifuge tube and flash-frozen with liquid nitrogen.…”
Section: Intestinal Gene Expressionmentioning
confidence: 99%
“…Dietary phosphate is absorbed passively via the nonsaturable paracellular pathway and actively via the saturable transcellular pathway. 54 , 117 , 118 , 119 Although it was previously believed that the active transcellular phosphate transport pathway was responsible for the majority of phosphate absorption, there is a growing body of evidence that the paracellular pathway is the dominant site of gastrointestinal phosphate absorption when luminal phosphate concentrations are high, 23 , 120 , 121 consistent with the consumption of a Western diet. 110 The paracellular route, in which phosphate passes through the tight junctions between the cell membranes, is the major phosphate absorption pathway under normal dietary conditions that contain high amounts of phosphate.…”
Section: Ckd-mbd Is a Significant Risk Factor For CV Mortalitymentioning
confidence: 99%
“… 110 The paracellular route, in which phosphate passes through the tight junctions between the cell membranes, is the major phosphate absorption pathway under normal dietary conditions that contain high amounts of phosphate. 120 , 121 , 122 , 123 Given this new knowledge and the understanding that maladaptive hyperabsorption of phosphate limits the efficacy of low phosphate diets and phosphate binders, 21 , 22 there is a call for new therapies that leverage these data to effectively control phosphate and avoid the negative outcomes associated with hyperphosphatemia and CKD-MBD.…”
Section: Ckd-mbd Is a Significant Risk Factor For CV Mortalitymentioning
confidence: 99%